Balancing the efficiency, stability, and cost potential for organic solar cells via a new figure of merit - Yang, Wenyan; Wang, Wei; Wang, Yuheng; Sun, Rui; Guo, Jie; Li, Hongneng; Shi, Mumin; Guo, Jing; Wu, Yao; Wang, Tao; Lu, Guanghao; Brabec, Christoph; et al. (Joule, 2021)
In spite of the great success in device efficiency resulting from the excessive design of photovoltaic materials, the stability and cost issues concerning basic commercial requirements of organic solar cells (OSCs) remain unresolved or controversial, slowing down the introduction of market-ready applications. We proposed an exciting discovery that as the active layer thickness decreases, the thermal stability increases gradually, even exceeding 100% of the initial efficiency under 150°C thermal stress. This trend was further confirmed by investigating thermodynamics and kinetics of morphology evolution for PM6:Y6 as a reference example. Extended research found that there is a similar correlation between photo-thermal stability and blend thickness. Consequently, a new reliable industrial figure of merit (i-FOM2.0), including four main factors: efficiency, photo-thermal stability, synthesis complexity, and active layer thickness, is presented here. Our work provides a promising trade-off strategy for reducing efficiency-stability-cost gap and accelerates the commercialization of OSCs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: active layer thickness; figure of merit; organic solar cells; photo-thermal stability; thermal stability